Aspek Hukum Penyerahan Sebagian Pelaksanaan Pekerjaan Kepada Perusahaan Lain (Outsourcing) - M Fauzi (Jurnal Risalah Hukum, 2006)
One of entrepreneur’s efforts to make efficiency in their company management is applying an outsourcing that is giving one or several divisions of their company to another company. However, realizations of this method obtain criticisms. Because implementation of out sourcing avowed give more harm for employees. Outsourcing is an old system that applying in Indonesian matters pertaining to labor fields. However only now arranged in article 64, 65 and 66 UU Nomor 13 Tahun 2003 tentang Ketenagakerjaan and Keputusan Menteri Tenaga Kerja dan Transmigrasi Republik Indonesia No.Kep.101/Men/VI/2004 Tahun 2004 tentang Tata Cara Perijinan Perusahaan Penyedia Jasa Pekerja/Buruh. The slight of rule in a code, which regulate outsourcing, cause many unfinished problem. The problem in labor relations, still not clear the criteria of supporting field in the some company and other problems in a row with prosperity of company management system, require regulation to secure employee rights. Keywords: outsourcing, hubungan kerja (relation), perjanjian pemborongan, perusahaan penyedia jasa (company of service), pekerja/buruh (labor).